Principles of maintenance of the informational security of Ukraine - Олійник, Олег Вікторович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article analyzes the principles of information security as a component of national security of Ukraine. Аuthor substantiates that effective planning, organization and management of information security today can not be achieved if not identified appropriate scientific principles. In this connection one of the important aspects of this problem is the necessity to define the basic scientific principles on which it is advisable to develop information security of Ukraine. It is noted that detection of capabilities and ways of solving the providing of information security should be preceded by an analysis of existing in legal science of principles of organization and management of information science. During his research author adhered the generalized definition of information security as such a state of society that naturally occurs where information security is the main guarantor of all resources and social transformations: the introduction of truly humanistic relations, socioeconomic development and protection of national interests. Consideration of information security was done on the methodological basis from the perspective of each functional orientation principle. Materials of analysis also provide an opportunity to assess a number of common mistakes in forming a system of principles, and in forming of separate principles. The article noted, firstly, that the authors of most systems of principles do not provide them, unfortunately, features of the system. In addition, violated the requirement of accordance of these principles together a specific aim of functioning of the system, part of which can be introduced simultaneously some methodological, administrative, legal and other principles. Justification of certain system of principles of information security means the increase of methodological adequacy of organizational information security of socio-economic condition of the state. Based on the strong methodological basis, informational security of the state begins to function as a systemic formation. Other words the basis for the definition and implementation of the basic principles of management should be laid their a conceptual complementarity, aimed at achieving a balance of functional, theoretical, methodological approaches and means to ensure the effectiveness of real current system of information policy.